Projected Land Evaporation and Its Response to Vegetation Greening Over China Under Multiple Scenarios in the CMIP6 Models. Issue 9 (10th September 2021) - Lu, Jiao; Wang, Guojie; Li, Shijie; Feng, Aiqing; Zhan, Mingyue; Jiang, Tong; Su, Buda; Wang, Yanjun
Abstract: Land evaporation (ET) is of great significance in climate change research, water resource management, and numerical weather forecasting. In this study, Ridge Regression Method and Sensitivity Analysis Methods have been used to study the projected land evaporation changes over China, and its response to vegetation greening under low (Shared Socioeconomic Pathway [SSP]1‐2.6), medium (SSP2‐4.5), and high (SSP5‐8.5) forcing scenarios during 2020–2099, based on 16 of the latest generation of Earth System Models (ESMs) taking part in the Coupled Models Intercomparison Project Phase 6. Land evaporation is projected to significantly increase under all climate change scenarios, especially in the southern China where there is a humid climate. The influencing factors, including precipitation, air temperature, solar radiation, and leaf area index (LAI), are analyzed; LAI is indicated to dominate the interannual variations of land ET, contributing over 40% of the interannual variance in the warming climates. However, the sensitivity of land ET to vegetation greening is found to generally reduce along with the increasing radiation forcing levels. Such a reduced sensitivity is particularly true when making intermodel comparisons, possibly due to the uncertainties of vegetation parameterizations in different models. This study reveals the response of land ET to vegetation greening under multiple climate change scenarios, which may help to understand the essential role of vegetation in water cycle and provide support for future water resource management. Key Points: Land evaporation (ET) is projected to significantly increase under Shared Socioeconomic Pathway (SSP)1‐2.6, SSP2‐4.5, and SSP5‐8.5 scenarios over China during 2020–2099 Among all influencing factors, leaf area index dominates the interannual variations of projected land ET, explaining over 40% of the total ET variance Land ET sensitivity to vegetation greening is reduced with the increasing radiation forcing levels, especially when models are compared